2021
DOI: 10.3390/ijms22063101
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mechanisms Mediating Methylmercury Neurotoxicity and Neuroinflammation

Abstract: Methylmercury (MeHg) toxicity is a major environmental concern. In the aquatic reservoir, MeHg bioaccumulates along the food chain until it is consumed by riverine populations. There has been much interest in the neurotoxicity of MeHg due to recent environmental disasters. Studies have also addressed the implications of long-term MeHg exposure for humans. The central nervous system is particularly susceptible to the deleterious effects of MeHg, as evidenced by clinical symptoms and histopathological changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 221 publications
(447 reference statements)
0
31
0
8
Order By: Relevance
“…Mercury has been well established as a neurotoxic factor, including its involvement in several malignancies as a result of organic mercury exposure (mostly methylmercury, MeHg) via dietary consumption (e.g., contaminated seafood, grains etc. ), medical treatment (e.g., syphilis treatment or teething powder), occupational settings (e.g., chronic exposure to mercury vapors) or any other form of exposure to mercury pollution in the environment [ 49 , 50 ].…”
Section: Mercury Poisoning and Its Link To Developmental Disabilities And Autismmentioning
confidence: 99%
“…Mercury has been well established as a neurotoxic factor, including its involvement in several malignancies as a result of organic mercury exposure (mostly methylmercury, MeHg) via dietary consumption (e.g., contaminated seafood, grains etc. ), medical treatment (e.g., syphilis treatment or teething powder), occupational settings (e.g., chronic exposure to mercury vapors) or any other form of exposure to mercury pollution in the environment [ 49 , 50 ].…”
Section: Mercury Poisoning and Its Link To Developmental Disabilities And Autismmentioning
confidence: 99%
“…Chronic exposure to Hg can result in a number of health consequences, including disorders of the nervous system and kidneys ( Johnson-Arbor et al, 2021 ; Novo et al, 2021 ). Metallic Hg enters the body via inhalation.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological and experimental studies have reported the vulnerability of the developing brain to environmental pollutants such as MeHg, the most toxic form of mercury, including a decrease in cell proliferation in the developing neural tube [ 7 , 8 , 9 , 10 ]. Several mechanisms have been suggested, including negative effects on neurotransmitter systems, induction of oxidative stress, microtubule disruption, and intracellular calcium homeostasis disturbance [ 12 , 13 , 14 , 15 ]. The fundamental toxicological mechanism related to the CNS damage appears to rely on the induction of an excessive amount of synaptic glutamate (i.e., inhibition of reuptake by astrocytes), as well as stimulation of neuronal release of this neurotransmitter, consequently leading to excitotoxicity and cell death [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%